How exposure to logos and logo varieties fosters brand prominence and freshness. Issue 7 (16th November 2015) - Sääksjärvi, Maria; van den Hende, Ellis; Mugge, Ruth; van Peursem, Nicolien
Abstract : Purpose: – This study aims to propose that a brand can be kept both prominent and fresh by using existing logos as well as logo varieties (i.e. slight modifications to the brand's existing logo). Design/methodology/approach: – In two experimental studies, the authors exposed respondents to either the existing brand logo or to logo varieties, and examined their influence on brand prominence and freshness. Findings: – The findings suggest that consumers subconsciously process logo varieties to which they are exposed in a similar way as they subconsciously process the existing logo of the brand, making both types of logo exposure effective for building brand prominence and freshness. Research limitations/implications: – It would also be worthwhile to study the effect of logo varieties using other dependent measures than the ones employed in this study, such as purchase intent and behavioral measures (such as consumption behaviors). Practical implications: – This research shows that logo varieties can be used alongside the existing brand logo to build prominence and freshness. These findings diverge from the findings typically reported in the branding literature that state that consumers resist changes to logos. Originality/value: – This research not only demonstrates that exposure to logo varieties and existing logos evokes automatic effects (both types of logos outperform a control group in fostering brand-related outcomes) but also confirms that exposing consumers to the existing logo or logo varieties give less differential effects than one may think.